Research on the Applicability of the MFN Clause in BITs in the Dispute Settlement Procedure (Asian Journal of Social Science Studies, 2022)
There is no doubt that the MFN clause in BITs applies to substantive matters, but there are great differences on the application of procedural matters. This paper first expounds the MFN clause in BITs, then discusses the dispute over the application of the MFN clause in dispute settlement, and finally makes an evaluation on the dispute.